Glycosaminoglycans: key players in cancer cell biology and treatment - Afratis, N.; Gialeli, C.; Nikitovic, D.; Tsegenidis, T.; Karousou, E.; Theocharis, A. D.; Pavao, M. S.; Tzanakakis, G. N.; Karamanos, N. K. (FEBS JFEBS J, 2012)
Glycosaminoglycans are natural heteropolysaccharides that are present in every mammalian tissue. They are composed of repeating disaccharide units that consist of either sulfated or non-sulfated monosaccharides. Their molecular size and the sulfation type vary depending on the tissue, and their state either as part of proteoglycan or as free chains. In this regard, glycosaminoglycans play important roles in physiological and pathological conditions. During recent years, cell biology studies have revealed that glycosaminoglycans are among the key macromolecules that affect cell properties and functions, acting directly on cell receptors or via interactions with growth factors. The accumulated knowledge regarding the altered structure of glycosaminoglycans in several diseases indicates their importance as biomarkers for disease diagnosis and progression, as well as pharmacological targets. This review summarizes how the fine structural characteristics of glycosaminoglycans, and enzymes involved in their biosynthesis and degradation, are involved in cell signaling, cell function and cancer progression. Prospects for glycosaminoglycan-based therapeutic targeting in cancer are also discussed.
Afratis, NikosGialeli, ChrisostomiNikitovic, DraganaTsegenidis, TheodoreKarousou, EvgeniaTheocharis, Achilleas DPavao, Mauro STzanakakis, George NKaramanos, Nikos KengResearch Support, Non-U.S. Gov'tReviewEngland2012/02/16FEBS J. 2012 Apr;279(7):1177-97. doi: 10.1111/j.1742-4658.2012.08529.x. Epub 2012 Mar 12.
Keywords: Chondroitin Sulfates/chemistry/metabolism; Disease Progression; Glycosaminoglycans/*chemistry/*metabolism; Humans; Hyaluronic Acid/chemistry/metabolism; Intercellular Signaling Peptides and Proteins/metabolism; Neoplasms/pathology/*physiopathology/*therapy; Signal Transduction/physiology